2006
DOI: 10.1080/10610270500398706
|View full text |Cite
|
Sign up to set email alerts
|

Design, Syntheses and Extraction Properties of NovelBis-calix[4]arene andTris-calix[4]arene Containing Two Kinds of Calix[4]arene Derivative Units

Abstract: By condensation of calix[4]arene 1,3-bis-hydrazide derivative 5 and calix[4]arene mono-benzaldehyde derivative 2, and then intramolecular bridging with triethylene glycol ditosylates, two novel tris-calix[4]arenes 6 and 7 containing two kinds of calix[4]arene derivative units were prepared in reasonable yield. When reacting compound 5 with calix[4]arene 1,3-bis-benzaldehyde derivative 3, novel bis-calix[4]arene 8 containing two different calix[4]arene derivative units was obtained in high yield. The extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…They suggested that the bulky calix [4]arene core is remote from the nickel centre, a fact observed in the X-ray studies, resulting in an uncrowded metal environment which facilitates the reductive elimination steps. The group of Schmutzler, Börner and co-workers have also looked at the rhodium(I) catalysed hydroformylation of olefins, using calix [4]arene derivatives containing phosphorus diamides (21)(22)(23)(24)(25) [38][39][40] (Fig. 14).…”
Section: Catalysismentioning
confidence: 98%
See 1 more Smart Citation
“…They suggested that the bulky calix [4]arene core is remote from the nickel centre, a fact observed in the X-ray studies, resulting in an uncrowded metal environment which facilitates the reductive elimination steps. The group of Schmutzler, Börner and co-workers have also looked at the rhodium(I) catalysed hydroformylation of olefins, using calix [4]arene derivatives containing phosphorus diamides (21)(22)(23)(24)(25) [38][39][40] (Fig. 14).…”
Section: Catalysismentioning
confidence: 98%
“…They believe that this alternative mechanism accounts for the faster kinetics of complexation exhibited by the calix [4]semitubes. Yang et al have also looked at some bis(calix [4]arene) derivatives, particularly with regard to the complexation of either metal cations or amino acids [22][23]. They have reported the synthesis of a bis(calix [4]arene) composed of a calix [4]arene unit and a thiacalix [4]arene unit (4) (Fig.…”
Section: Biological Applicationsmentioning
confidence: 98%
“…一般地, 通过双官能团试剂与杯芳烃直接缩合, 可得到结构对称 的双杯芳烃, 但由于多羟基的桥联方式多样, 产率一般 不高, 分离较复杂 [4~6] . 另一方面, 通过先于杯芳烃单 元引入活性官能团, 再进一步与另一杯芳烃单元反应可 得到含两种不同结构单元的双杯芳烃, 由于步骤较为复 杂, 这种间接合成法报道较少 [7][8][9][10] . 如果用四条桥联链 [11,12] .…”
Section: 杯芳烃是有机超分子领域广受瞩目的人工合成主unclassified
“…A tris-calixarene with hydrazido links was obtained in three steps starting from diester 239. 78 Treatment of the latter with hydrazine gave nearly quantitative hydrazide 240 which was subsequently condensed with aldehyde 205 to afford 241 in 80% yield. This multicalixarene was assessed in the extraction of various cations from water into CHCl 3 .…”
Section: Bis-calixarenes With Linkers Containing N-donorsmentioning
confidence: 99%